Filariasis caused by nonperiodic form of Brugia ma/ayi among transmigrants in East Kalimantan. - FA Sudjadi FA Sudjadi (Journal of the Medical Sciences (Berkala Ilmu Kedokteran), 1998)
A new subspecies of sylvanic or human filarial worm, i.e. nonperiodic form of Brugia malayi Lichtenstein, was recently discovered in East Kalimantan, which was highly prevalent among Dayak indigenous people living in the deep forest. This paper reports the filarial infections among transmigrants coming from Java who have been resettled for about 30 years in the UPT (unit of transmigration resettlement) of Petung, Penajam district, Pasir regency. Higher filarial infections were recorded among transmigrants living in hilly parts of the UPT, such as those found in Gunungrejo subvillage, with a micro-filarial rate of 6.3%, clinical rate of 8,1% or filariasis rate of 12,9%, out of 520 people examined. In more swampy areas, such as those found in Kedungrejo subvillage, the parasite Infection rate was much lower, and was recorded only 3,1%, out of 578 people examined. The result of blood or clinical examinations carried out in this research also indicated that male and older Inhabitants or transmigrants who have stayed longer in Kalimantan have a higher risk of Infection.Key words: transmigrants - Brugia malayi - nonperiodic form - sylvanic filaria - mansonia